(untitled) (Research, Society and Development, 2020)
In many countries vitamin A deficiency is the most commonly found, and that is why it is important that this micronutrient supplementation be done, and that is why in Brazil there is a Supplementation Program in vitamin A. The National Supplementation Program in Vitamin A is part of health actions by the Ministry of Health aimed at combating this hypovitaminosis, and supplementation with high doses is the most effective method to eradicate this problem. This is an excerpt from a study with secondary data available in the Information System of the Unified Health System (SUS), collected between January and May 2020, with the data available for the year 2015. After statistical processing with the test analysis of variance ANOVA a criterion, the value of p = 0.7829 was found, this being significantly non-statistical, this may be due to the extremes of the values ​​found in the public domain data. In view of the above, it is observed that even if only one city exceeds the supplementation target, the National Vitamin A Supplementation Program is effective in combating hypovitaminosis in children.